2022
DOI: 10.3389/fphar.2022.941955
|View full text |Cite
|
Sign up to set email alerts
|

Arecae pericarpium water extract alleviates chronic pancreatitis by deactivating pancreatic stellate cells

Abstract: Chronic pancreatitis (CP) is a chronic inflammatory disease of the pancreas with irreversible morphological changes. Arecae pericarpium (ARP), known to improve gastrointestinal disorders, has not yet been reported to inhibit fibrosis in CP. Therefore, we investigated the beneficial effects of ARP on cerulein-induced CP. Cerulein (50 μg/kg) was administered intraperitoneally to mice every hour, six times a day, four times a week for a total of 3 weeks to induce CP. To ascertain the prophylactic effects of ARP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…These texts record various medicinal combinations involving AN, demonstrating its efficacy in treating conditions such as oppressive sensations in the chest, heartache, lower back pain, urinary and bowel irregularities, intestinal parasitism, athlete’s foot, and oral ulcers. Subsequent scholarly investigations into the pharmacological properties of AN extracts have revealed their antidepressant, antimicrobial, anti-aging, insecticidal, anti-osteoporotic, hepatoprotective, and anti-inflammatory effects ( Dar et al, 1997 ; Lee and Choi, 1999 ; Pithayanukul et al, 2009 ; Li et al, 2017 ; Jam et al, 2021 ; Sharaf et al, 2021 ; Kweon et al, 2022 ; Puyathorn et al, 2022 ). In a recent study, extracts from arecae semen demonstrated inhibitory effects on snake venom ( More et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…These texts record various medicinal combinations involving AN, demonstrating its efficacy in treating conditions such as oppressive sensations in the chest, heartache, lower back pain, urinary and bowel irregularities, intestinal parasitism, athlete’s foot, and oral ulcers. Subsequent scholarly investigations into the pharmacological properties of AN extracts have revealed their antidepressant, antimicrobial, anti-aging, insecticidal, anti-osteoporotic, hepatoprotective, and anti-inflammatory effects ( Dar et al, 1997 ; Lee and Choi, 1999 ; Pithayanukul et al, 2009 ; Li et al, 2017 ; Jam et al, 2021 ; Sharaf et al, 2021 ; Kweon et al, 2022 ; Puyathorn et al, 2022 ). In a recent study, extracts from arecae semen demonstrated inhibitory effects on snake venom ( More et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Administering ARP extract significantly improved glandular atrophy and inflammation in the pancreas, while also inhibiting collagen accumulation. The water extract from ARP exhibited the ability to impede the constituents of the extracellular matrix (ECM), specifically targeting alpha-smooth muscle actin (α-SMA), collagen I, and fibronectin 1 (FN1) in both pancreatic tissue and pancreatic stellate cells (PSCs) [ 78 ]. Furthermore, the water extract from AN demonstrated a notable anti-inflammatory effect on carrageenan-induced paw edema in mice and rats [ 75 ].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…The filtrate was stored at 4 • C until use. We previously reported that the aqueous AP extract contains approximately 0.604% of 4-hydroxybenzoic acid and 0.388% of (+)-catechin as bioactive compounds [19].…”
Section: Sample Preparationmentioning
confidence: 99%